Respuesta :
Answer:
B and D
Step-by-step explanation:
Given
x² - x - 12
Consider the factors of the constant term (- 12) which sum to give the coefficient of the x- term (- 1)
The factors are - 4 and + 3 , since
- 4 × 3 = - 12 and - 4 + 3 = - 1 , then
x² - x - 12 = (x - 4)(x + 3) ← in factored form
Answer:
B and D
Step-by-step explanation:
If you call s=-1 the coefficient of x and p=-12 the constant term, you must find two numbers whose sum is s and product is p.
In this case the two numbers are -4 and +3 in fact:
(-4)+(+3)=-1=s
(-4)*(+3)=-12=p
The polynomial can therefore be written as
(x-4)(x+3)
If you want to check this result, just multiply and get:
(x-4)(x+3)=x^2+3x-4x-12=x^2-x-12